(3GdfbhO hGdQOhOs - (3eMeO Hf jhSa Hf Ydj Hf SYjO, TeS GdOjf GdcQeGfj , (B786 (3g` s
(3ChdgG (B:s
(3bhdg GdefhYI Ci GdLGYdI ddaYd fhYkG s
(3BNQgG (B:s
(3CQTOfG Gddg hEjGce deG jfaYfG ai GdOfjG hGdBNQI s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3eUOQ GbJfGA GdCUd (B:s
(3GdeJMa GdYQGbi (B- (3HZOGO (B(831) s
Keywords: (3CUhd Gdabgs